ANALISIS PENGARUH KEBISINGAN TERHADAP KESEHATAN KESELAMATAN KERJA KARYAWAN PT CHAROEN POKPHAND INDONESIA - Mohammad Faris; Setyaningrum, Ratih (Universitas Kadiri, 2026)
PT Charoen Pokphand Indonesia Feedmills is one of the manufacturing companies engaged in the animal feed industry, which focuses on the manufacture of broiler animal feed, laying hen animal feed, pig animal feed, and quail animal feed. In carrying out activities, workers are faced with barges and machines. So that prevention and mitigation of hazards is a misconsideration to ensure the health and safety of workers. This study aims to determine the relationship between noise factors and health disorders, including noise intensity, noise sources, and the use of PPE. Using the method The research method used to identify risks is Job Safety Analysis (JSA). Therefore, K3 risk analysis and control suggestions were obtained at the highest risk, namely hearing impairment due to machine noise, and communication disturbances.